Assessment of Growth, Lipid Metabolism and Gene Expression Responses in Senegalese Sole Larvae Fed With Low Dietary Phospholipid Levels - Hachero-Cruzado, Ismael; Rodriguez-Rua, Ana; Torrent, Ivana; Roman-Padilla, Javier; Manchado, Manuel (Frontiers in Physiology, 2020)
Phospholipids (PL) are essential molecules for larval growth and development. In this study, growth, lipid metabolism and gene expression responses associated with different dietary PL levels in pelagic sole larvae were evaluated. In a first trial, the long-term effects on growth and survival of two experimental microdiets (MD) containing high (High-PL) or low (Low-PL) PL levels were tested and compared to a diet based on live prey (rotifers). The MD were supplied from 3 to 10 days post-hatch (dph) and Artemia from day 8 to 29 dph. High-PL fed larvae had higher dry mass (1.2-fold) than Low-PL fed larvae at 8 dph and both MD were smaller (2.9-fold) than larvae fed live preys. However, a compensatory growth (33% between 8-20 dph) occurred when MD were substituted by Artemia and by the end of the trial no significant differences in mass or survival occurred between the dietary treatments. In a second trial, growth, lipid metabolism and gene expression profiles of larvae fed with MD up to 8 dph were analyzed. Growth data confirmed that mass of larvae fed with High-PL was higher (1.3-fold) than the those fed Low-PL and they had lower levels of triacylglycerol (2.8-fold), cholesterol (1.2-fold) and cetoleic acid (1.7-fold). Histological analysis indicated an excess of lipid vacuoles in larvae fed with Low-PL and the expression analysis revealed a coordinated response to enhance lipid mobilization since the expression of genes involved in PL intermediate synthesis, PL remodelling as well as eight apolipoprotein was up-regulated. The down-regulation of apolipoprotein apob2 in larvae fed with Low-PL indicated a specific regulation by PL levels. The present work provides insight into the responses associated with dietary PL in early fish larvae, which will be of use for future studies aimed as designing effective larval sole diets.